インドネシア語における「Se~」という接頭辞 - Gapur, Abdul; Taulia, Taulia; Pujiono, Mhd. (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2022)
This paper aims to describe the function of the prefix “se-” in Bahasa Indonesia. The approach is qualitative and uses descriptive methods. Data are words that begin with "se-" in the Indonesian dictionary. As a result, "se-" has seven meanings in Indonesian, "one," "all," "same," "similar," "at the same time," "how many," and "most." In addition to the meanings listed above, several words beginning with "se-" are single words that stand alone (free morphemes), such as "senyawa," "seberang," "sekarang," "selada," "sekutu," and "setawar," among others.